Reliability Evaluation Of Multiprocessor System Based On The Balanced Complete Multipartite Graphs - Yu, Zhecheng; Xu, Liqiong (Computer journal, 2024)
Reliability evaluation of multiprocessor systems is of significant importance in the design and maintenance of multiprocessor systems. Based on edge-connectivity, more refined quantitative indicators for the reliability of multiprocessor systems have been introduced. The extra edge-connectivity and the component edge-connectivity, as two important parameters to evaluate the robustness of multiprocessor systems, are explored extensively. In this paper, we determine the $h$-extra edge-connectivity and the $(g+1)$-component edge-connectivity of the balanced complete $t$-partite graph $K_{r}^{t}$ for $t, r≥ 2$, where $1≤ h ≤ \lfloor tr/2 \rfloor$ and $2≤ g ≤ tr-1$.